The genera Anafroptilum Kluge, 2011 and Neocloeon Traver, 1932, reinstated status, in North America, with remarks about the global composition of Centroptilum Eaton, 1869 (Ephemeroptera: Baetidae) - Jacobus, Luke M.; Wiersema, N. A. (Zootaxa, 2014)
The mayfly genus Centroptilum Eaton, 1869, s.s., (Ephemeroptera: Baetidae), as presently understood, is not known to occur in North America. Nearctic species recently classified there belong either to Anafroptilum Kluge, 2011 or to Neocloeon Traver, 1932, reinstated genus. The North American endemic Neocloeon differs fundamentally from Anafroptilum in that it possesses a patella-tibial suture on the foreleg of larvae and female adults, a characteristic that is shared with certain other baetid genera. Neocloeon includes the obligate parthenogen N. triangulifer, new combination, and a sexual species, N. alamance, reinstated combination. Nearctic Anafroptilum include: A. album (McDunnough, 1926), new combination, A. asperatum (Traver, 1935), new combination, A. bifurcatum (McDunnough, 1924), A. conturbatum (McDunnough, 1929), new combination, A. minor (McDunnough, 1926), new combination, A. ozarkense (Wiersema & Burian, 2000), new combination, A. semirufum (McDunnough, 1926), new combination, and A. victoriae (McDunnough, 1938), new combination. Further study will be required to determine the species composition of Anafroptilum and Centroptilum, s.s., in the Palearctic and Oriental realms. Anafroptilum and Neocloeon are part of the Cloeon complex of genera, but Centroptilum, s.s., is not.